(3GdeYGLe GdMOjKI ddbQBf GdcQje (B: s (3OQGSI ai GdeGOI h GdefgL (B/ s - (3YQaI Mdei cGeds; (3eMeO MSf YHOGdYRjR (B: s ((3GdbGgQI (B: s (3YQaI Mdei cGed (B: s, 2010)
(3bGeJ gPg GdOQGSI Mhd eYGLe CdaGX GdbQBf GdcQje GdMOjKI GdJi JgJe HJbOje GdcdeI h eYGfjgG GdeNJdaI ai BjGJ GdbQBf(B: (3eY HjGf GdeUGOQ GdJi LeYJ efgG gPg GdeGOI(B: (3h WQjbI JQJjH GdeOGNd OGNd cd eYLe ef GdeYGLe GdJi hbY YdjgG GdGNJjGQ cfeGPL dgPg GdeYGLe(B: (3eY HjGf hXGFa GdeYLe GdeNJdaI; cWQb TQM GdeYfi(B: (3h GdeYdheGJ GdUQajI h GdfMhjI(B: (3h eYdheGJ GdGSJYeGd(B: (3h GdeYdheGJ GdGTJbGdjI(B: (3h GdeYdheGJ GdehShYjI(B: (3eY EjQGO CeKdI ef gPg GdeYGLe JHjf cjajI JCdjagG s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe Yde GddZI h GdOQGSGJ GdSGejI h GdTQbjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdCdaGXs; (3GdbQBfs; (3GdeYLes